Kemuliaan Berita Injil dalam Konstruksi Kesederhanaan Cerita: Efektivitas Metode Cerita Bagi Anak - Blegur, Romelus; Gea, Leniwan Darmawati (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2025)
Stories are an effective communication method to convey the meaning of news in a simple and interesting way. This method is also relevant in all related contexts, as well as all age groups. Until now, stories are still a popular method. Apart from its general use, stories are also a method used in the Bible to convey the truth as was done many times by Jesus, even now it is also seen in the practice of preaching the Gospel in the church. The purpose of this research is to investigate the glory of the Gospel message in the simplicity of the story with a focus on its effectiveness through preaching the Gospel to children. The method used in this research is a library research method by analyzing texts sourced from online and printed literature. The results of this research are that the story method is effective for preaching the Gospel to children. The supporting factor is that, this method has been predominantly used in the Bible with a percentage of 75%. Apart from that, the story method is effective as a forum for preaching the Gospel, even though the Gospel message is constructed simply according to children's capacities, it does not erode the glory of the Gospel message.